Approach, ability, aftermath: a psychological process framework of unethical behavior at work - Moore,C; Gino,F (The Academy of Management Annals, 2017)
Many of the scandalous organizational practices to have come to light in the last decade—rigging LIBOR, misselling payment protection insurance, rampant Wall Street insider trading, large-scale bribery of foreign officials, and the packaging and sale of toxic securities to naïve investors—require ethically problematic judgments and behaviors. However, dominant models of workplace unethical behavior fail to account for what we have learned from moral psychology and cognitive neuroscience in the past two decades about how and why people make the moral decisions they do. In this review, we explain how intuition, affect, physiology, and identity support and inform more deliberative reasoning process in the construction and enactment of moral behavior. We then describe how these processes play into how individuals approach a potential moral choice, whether they have the ability in the moment to enact it, and how it is encoded in the action' aftermath, feeding back into future approaches. Throughout, we attend to the role of organizational context in influencing these processes. By reviewing this large body of research and presenting a new framework that attempts to integrate these new findings, our hope is to motivate new research about how to support more moral workplace behavior that starts from what we know now.